2014
DOI: 10.1210/jc.2013-2017
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Subcellular Localization of Estrogen Receptors α and β in Human Fetal Brown Adipose Tissue

Abstract: The expression of both ERα and ERβ in human fBAT suggests a role for estrogen in its development, primarily via ERα. In addition, our results indicate that fBAT mitochondria could be targeted by estrogens and pointed out the possible role of both ERs in mitochondriogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…Emerging work points towards a role for estrogen receptors (ER), in particular ERα, in fetal adipogenesis, although this study was limited by a sample size of n = 1 at each time point [66]. Little work has been done to look at the effect of sex steroids on their autologous receptors.…”
Section: Direct Effectsmentioning
confidence: 99%
“…Emerging work points towards a role for estrogen receptors (ER), in particular ERα, in fetal adipogenesis, although this study was limited by a sample size of n = 1 at each time point [66]. Little work has been done to look at the effect of sex steroids on their autologous receptors.…”
Section: Direct Effectsmentioning
confidence: 99%
“…The dependence of metabolic [13,14] and inflammatory [15] processes on ERs in both genders was later confirmed in mouse models deficient in Erα , Erβ , or both [16]. The absence of Erα in both male and female mice resulted in increased white adipose tissue mass (WAT) and impaired insulin resistance [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that the ER-β expression pattern could be a reflection of prepubertal sex differences. There is evidence that both ER-α and ER-β were expressed in human fetal brown adipose tissue(fBAT), with ERα being dominant (Velickovic et al, 2014). The authors demonstrated that ER-β was present only in mature brown adipocytes while ER-α was in mature adipocytes and preadipocytes, and suggested a dominant role for ER-α in its development and, fBAT mitochondria could be targeted by estrogens (Velickovic et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that both ER-α and ER-β were expressed in human fetal brown adipose tissue(fBAT), with ERα being dominant (Velickovic et al, 2014). The authors demonstrated that ER-β was present only in mature brown adipocytes while ER-α was in mature adipocytes and preadipocytes, and suggested a dominant role for ER-α in its development and, fBAT mitochondria could be targeted by estrogens (Velickovic et al, 2014). Finally, there is a report on the HCG/LH receptor expression in human preadipocytes, and our data about LHR expression in rat adipose tissues confirm the finding (Dos Santos et al, 2007).…”
Section: Discussionmentioning
confidence: 99%